The Effect of Early Movements of Swollen Lymph Nodes Caused by COVID-19/ Vaccine of COVID-19 on Recovery - Usama A. Aljameey; Stephen R. Bergman (University Library System, University of Pittsburgh, 2022)
Background: The swelling of the lymph nodes may raise some concerns and anxiety for people after getting the vaccination, especially for COVID-19. Many women seek medical attention for the enlarged lymph node due to the known relationship between lymph nodes and breast cancer. This research is intended to enrich the data of the most recent COVID-19 pandemic and the vaccines that were developed shortly after. The aim is to see if there is an effect of early movement of the swollen axillary lymph nodes caused by the COVID-19 vaccination and to enrich the data of the most recent COVID-19 pandemic and its developed vaccines shortly after. Methods: A voluntary survey was used to collect data from recently vaccinated individuals. Data were analyzed for associations between early movement and resolution of lymphadenopathy. Results: 32 (20.38%) of 157 participants reported swelling of axillary lymph nodes that resulted from COVID-19 vaccination.  Duration of swelling ranged from 1 to more than two weeks.  The early movement did not show a statistically significant reduction in the course of swelling. Conclusion: Early movement of areas affected with lymph node enlargement, whether active or passive, does not seem to cause additional side effects.  The effect of early action seems comparable to rest (see Fig.), although it may lessen erythema due to improved circulation, just like the newer concept of early movement after a skeletal injury has a better outcome than merely resting, which was the older method of recovery. However, the current data is limited to support the benefit of such a concept.